PENINGKATAN PRODUKTIVITAS IKAN SIDAT(Anguila sp.)DENGAN SISTEM POLIKULTUR - Gagan Garnawansah; Wulandari Suryaningtyas; Ach. Khumaidi (Samakia : Jurnal Ilmu Perikanan, 2017)
Eel (Anguilla sp.) is an export commodity that has high economic value, but in the development of cultivation encountered a problem on the treatment period. To reach consumption size it takes 12-16 months. To improve productivity and provide added value needs polyculture systems with tilapia which is easy in terms of its treatment and can stabilize water quality. The aim of this study was to determine the productivity of eels using polyculture systems with tilapia. The research was conducted at BLUPPB Karawang in February – April 2015, using six (6) pool of treatment. Three pools were used for activities with a polyculture system and three pools were used for the treatment of non-polyculture. The results showed that a polyculture system of eel and tilapia treated for 60 days can make a positive impact to the Specific Grow Rate (SGR) 0.98%, and Food Conversion Ratio (FCR) 1.09 when compared with non-polyculture with SGR (0,93) and FCR (1.23). The results of analysis of effort on polyculture systems can provide the added value of the tilapia harvest.